Literature Review: Adolescent Idiopathic Scoliosis - Angelita, Puja Rizkina (Biocaster : Jurnal Kajian Biologi, 2025)
Adolescent Idiopathic Scoliosis (AIS) is the most common spinal deformity seen by general practitioners, pediatricians, and spine surgeons in adolescents aged 10–18 years. Also known as “late-onset” scoliosis, AIS is typically characterized by a lateral curvature of the spine of ≥10° on radiological examination. This article aims to examine the characteristics, prevalence, diagnostic methods, and risk factors of AIS through a literature review. The method used was a literature review of several scientific articles from the PubMed, Scopus, and Google Scholar databases published within the past 10 years. The results of the study indicate that AIS is more common in females, with a global prevalence ranging from 0.47 to 5.2%. Physical examinations, such as the Adams forward bend test, are common initial screening methods for detecting postural abnormalities, such as rib hump or shoulder asymmetry. The conclusions of this review emphasize the importance of early detection of AIS to prevent progression of the disorder and long-term biomechanical complications.